Briefly Trained Medical Students Can Effectively Identify Rheumatic Mitral Valve Injury Using a Hand‐Carried Ultrasound. Issue 6 (24th January 2013) - Shmueli, Hezzy; Burstein, Yuval; Sagy, Iftach; Perry, Zvi H.; Ilia, Ruben; Henkin, Yaakov; Shafat, Tali; Liel‐Cohen, Noah; Kobal, Sergio L.
<x xml:space="preserve">Abstract</x> Background Rheumatic heart disease (RHD) is common and remains a major cause of morbidity, particularly in developing countries. Its diagnosis relies on expertise‐dependent echocardiographic studies. We evaluated the accuracy of briefly trained examiners in identifying RHD utilizing a hand‐carried cardiac ultrasound (HCU) device. Methods Three medical students received 8 hours of training in cardiac ultrasound, focused on assessment of rheumatic valve injury and its complications, using a prototype of HCU device, OptiGo. The students, blinded to the patients' medical condition, performed an auscultation‐based physical examination and a focused HCU study on volunteers and patients with known RHD. A standard echocardiography study was used to validate the results. Results Each student performed a physical examination followed by an HCU study on 45 subjects (mean age 57 ± 14 years, 52% men), 14 of whom (31%) had rheumatic mitral valve injury. The students' averaged sensitivity for diagnosing RHD by HCU examination was 81%, while specificity was 95%. The interrater agreement (kappa) of the 3 students' HCU study and the standard echocardiography examination were between 0.55 and 0.88 (P < 0.01), and among the students themselves between 0.57 and 0.74 (P < 0.01), as students 1 and 2 had better results than student 3. Auscultation‐based physical examination rendered low sensitivity (16%) for diagnosing rheumatic valve complications, namely mitral regurgitation and stenosis; however, it improved by 26% when students based their diagnosis on an HCU study. Conclusions The ability to detect rheumatic valve injury using a portable ultrasound device by operators who only received brief echocardiographic training is remarkably high. However, the diagnosis of RHD complications is only modest. This result highlights the utility of portable cardiac ultrasound devices operated by basically trained personnel as a valuable diagnostic tool for RHD.